Effectiveness of massage therapy to reduce bilirubin levels in neonates with hyperbilirubinemia a systematic review and metaanalysis - Natashia, Dhea; Rahmania, Sarah; Yulianti, Dian Anggur; Laily, Dayang; Istinganah, Istinganah; Humairah, Faradila (Journal of Midwifery and Nursing, 2024)
Hyperbilirubinemia in neonates is often a health problem that can cause serious complications such as encephalopathy, kernicterus, and even death if not treated properly. Currently, treatments focus on phototherapy, which despite its positive impact, also has the potential to cause negative effects such as diarrhea, dehydration, skin rash, blue baby syndrome, and skin darkening. Massage therapy is emerging as a potential intervention to reduce the need for phototherapy and lower bilirubin levels. Although massage therapy shows a positive impact, it has not been proven to be fully effective in lowering bilirubin levels in neonates with hyperbilirubinemia. The aim of this systematic review is to assess the effectiveness of massage therapy on reducing bilirubin levels in neonates with hyperbilirubinemia. In this review, 127 articles were selected, and the results showed that massage therapy was effective in reducing bilirubin levels in neonates. In conclusion, massage therapy can be implemented in health services as an effective approach to treat hyperbilirubinemia in neonates.